(untitled) (International Journal of Nursing Education, 2020)
The study was conducted to evaluate the effectiveness of Facilitated tucking on Physiological and Behavioral responses among neonates receiving Hepatitis B vaccination. Quasi experimental non-randomized control group design was adopted for the study. The structured questionnaire was developed to collect the data. The sample were selected by purposive sampling technique and data collection was carried out among 60 neonates in a selected hospital. Pretest and posttest conducted before and after facilitated tucking. The finding reveals that the physiological responses of ‘t’ value in heart rate was 3.01 respiration 1.52 and oxygen saturation 3.59 and behavioural responses of ‘t’ value was 5.6 which significant at p<0.05. It shows that Facilitated tucking was effective in enhancing physiological and behavioral responses among neonates. There was a significant association between the age, gender, weight of neonates with physiological and behavioural responses. The study concluded that providing facilitated tucking was very effective in enhancing physiological and behavioral responses among neonates.